Patient Perceptions of Wearable and Smartphone Technologies for Remote Outcome Monitoring in Total Knee Arthroplasties - Kurtz, Steven M.; Higgs, Genymphas B.; Chen, Zhongming; Koshut, William J.; Tarazi, John M.; Sherman, Alain E.; McLean, Scott G.; Mont, Michael A. (The Journal of Knee Surgery, 2022)
While there is enthusiasm for wearables and smartphone technologies in evaluating clinical outcomes among clinicians, less is known about the willingness of patients who have osteoarthritis (OA) to consent for remote outcome monitoring. We developed an Institutional Review Board-approved questionnaire to assess patient perceptions of remote monitoring technologies in a high-volume orthopaedic clinical center. Fifty total knee arthroplasty (TKA) patients (56% female; mean age: 61 years, range: 23–89) and fifty nonoperative OA knee patients (54% female; mean age: 58 years, range: 25–89) routinely consulted in the clinic as part of their OA treatment and consented to participate in the study. Patient perceptions were compared using Pearson's chi-square analyses with a significance threshold of p < 0.05. We found that TKA patients were more receptive to the use of smartphone apps (84 vs. 60%, p = 0.008) and wearable sensors (80 vs. 48%, p < 0.001) and learning to use custom wearables (72 vs. 38%, p = 0.002) than nonoperative OA knee patients as part of their treatment. Likewise, the majority of TKA patients were willing to use the global positioning system in their postoperative technology (54 vs. 18%, p < 0.001), especially if they were only active during certain circumstances (62 vs. 24%, p < 0.001). TKA patients also expressed willingness to have their body movement (68%), balance (70%), sleep (76%), and cardiac output (80%) tracked using remote technologies. Overall, we found that TKA patients were highly receptive to using wearable technology in their treatments, whereas nonoperative OA knee patients were generally unreceptive. Our study challenges the concept that current wearable technology approaches will be generally effective as a tool to remotely monitor all patients across the OA severity landscape.
Keywords: total knee arthroplasty; patient-reported outcomes; surveys; wearables; smartphones